Ações de qualificação na UFU: um olhar técnico para a formação de competências - Lima, Luís Sérgio Fernandes de (2019)
This study aims to verify whether the qualification actions, represented by Master and Doctorate degrees and resulting from the implementation of a Career Plan for Technical and Administrative Personnel in Education (in Brazilian Portuguese, Plano de Carreira dos Cargos Técnico-Administrativos em Educação - PCCTAE) in a federal institute for higher education, lead to competence acquisition through professional development in order to achieve institutional goals. In this study it was necessary to understand the term “competence”, as well as how it is interpreted in the literature and public services, in which it is used as a human resource management tool via Decree No. 5.7075 of February 23th, 2006, and supported by the National Program of Public Management and Debureaucratization (in Brazilian Portuguese, Programa Nacional de Gestão Pública e Desburocratização - GESPÚBLICA). Implementation of the legislation regarding “competence” has demonstrated to be suitable for universities, since the career plan of those organizations, implemented in 2005, featuring strong strategic appeal, encourages training and qualification through significant wage incentives. This research analyzes a corpus composed of Master and Doctorate courses, which were submitted by the Technical and Administrative Personnel in Education (in Brazilian Portuguese, Técnico-Administrativos em Educação - TAEs) of a federal institute for higher education in order to obtain incentives for professional qualification. The analysis aims to identify the link between competence and organizational goals by comparing positions, duties, areas of activity, and the earned titles. This parallel provided the means to verify the applicability of the acquired skills to the work routines, which is a requirement of the competence management, in order to achieve organizational objectives, which is an element of strategic management. The lack of an appropriate institutional development plan that establishes the essential procedures for people management to achieve organizational goals allows us to infer that qualification actions presented by TAEs are not truly associated to building skills.